Math help!

posted by .

I don't understand this.

Solve -5x - 6 = -6x^2


Rearrange to
6x^2-5x-6=0
(3x + 2)(2x - 3)= 0
Set each factor equal to zero and solve for x. I hope this helps.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Math

    I just don't understand this question: h(t)=A*b^x h(3)=4 h(5)=40 Solve for b Would you plug 3 into the x and set it equal to 4?
  2. math

    just an algebra question. how would you solve: (3x^2 +5)(3x^2 +5) ^ means power :] Since you have not given us an equation, it is impossible to "solve" your problam. Please repost with the complete equation, so we can help you. I hope …
  3. Math

    The graph of the equation y=4-x consists of all the points in the coordinate plane that satisfy the equation. List 5 points that satisfy y= 4-x. Also, what do you think is the minimum number of points you need to plot in order to draw …
  4. help...solving a polynomial....algebra

    solve this please....help me....12x(squared)+7x-10 Do you wish to factor this trinomial?
  5. Math/Physics

    The velocity v of a particle moving in the xy plane is given by v = (6.0t - 4.0t2) i + 4.0 j, with v in meters per second and t (> 0) is in seconds. What is the acceleration when t = 3.0 seconds?
  6. Math Repost!!Please Help!!!!

    6-y --------- y^2-27-24 well it should simplify to (6-y)/(y^-1) which then changes to y(6-y) which then equals y(6-y)=0 then you set both parts equal to zero and solve for xero y=0 and/or (6-y)=0 so y=0 or y=6 Did you mean for this …
  7. MATH

    HOW DO I SOLVE A QUADRATIC EQUATION BY FACTORING?
  8. algebra

    It is not solvable by that method, shanaid. You have to get all the numbers on the left, set them to equal zero, and factor. which method is used to solve this equation. x^2-9x-4=6 I would factor, move the six over, then factor i would …
  9. Math

    I don't understand this!!! If rstv=1 and stuv=0, which of the followin must be true?
  10. algebra

    3ax^2 - 27a You can factor that into 3a (x^2 - 9), which also equals 3a(x-3)(x+3). It is not clear from your question what you are supposed to do with that algebraic expression. If it were equal to zero, x would be +3 or -3. If you …

More Similar Questions